The Transcribed-Ultraconserved Regions: A Novel Class of Long Noncoding RNAs Involved in Cancer Susceptibility - Paola Scaruffi (The Scientific World Journal)
During recent years, novel approaches and new technologies have revealed a startling level of complexity of higher eukaryotes' transcriptome. A large proportion of the transcriptional output is represented by protein noncoding RNAs (ncRNAs) that arise from the “dark matter” of the genome. Focus on such sequences has revealed numerous RNA subtypes with several functions in RNA processing and gene expression regulation, and deep sequencing studies imply that many remain to be discovered. This review gives a picture of the state of the art of a novel class of long ncRNA known as transcribed-ultraconserved regions (T-UCRs). Most recent studies show that they are significantly altered in adult chronic lymphocytic leukemias, carcinomas, and pediatric neuroblastomas, leading to the hypothesis that UCRs may play a role in tumorigenesis and promising innovative future T-UCR—based therapeutic approaches.